Eksistensi Jaminan dalam Kontrak Pengadaan Gabah/ Beras pada Perum Bulog Divisi Regional Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
The binding of security in rice sales contract between Perum BULOG Yogyakarta Regional Division and contractors is carried out in a pawning manner (for money and periodical deposit used as the security), and personal security (for bank guaranty. The forms of default include supplying rice trim mill rice that is below the standard, overdue provision, short amount of supply, and supplying rice not from the product of rice mill agreed on in the contract. Some efforts to solve these problems include giving an addendum (grace period), obligation for compensation payment of 111000 to a maximum of 0,5% of the total shortage, and internal resolution. Thefactors preventing any claim for the security are : almost 80% of contractors can use the grace period offered, and the compensation payment is able to compensate the loss suffered by Perum BULOG. One of the reasons from theoritical bases is that the risk in a sales contract for measured and calculated commodity must be born by the buyer, which is Perum BULOG Yogyakarta Regional Division in this case.